The Psychological Dynamics of Domestic Violence Victims in Efforts to Improve Mental Health - Nadya Mahfudzah; Nor Fatmah (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2026)
Domestic violence (KDRT) is a form of social pathology with serious psychological consequences, particularly for children raised in such environments. This study aims to explore the subjective experience of a 20-year-old university student who has been exposed since childhood to verbal and psychological violence as well as emotional neglect by a paternal figure. Employing a qualitative phenomenological approach through in-depth interviews and observation, this research seeks to understand the psychological dynamics, mental health impacts, socio-academic functional impairments, and coping strategies developed by the subject under sustained adversity. Five central themes were identified: (1) repeated exposure to verbal and psychological violence; (2) emergence of psychological symptoms including flashbacks, anxiety, depressive patterns, and self-esteem disturbances; (3) cognitive impairment and academic performance decline; (4) adverse effects on social relationships and attachment patterns; and (5) resilience capacity through behavioral, cognitive, relational, and spiritual coping mechanisms. These findings affirm that the impact of domestic violence is pervasive and multidimensional, permeating all aspects of the victim's life. Nevertheless, amid significant adversity, the subject demonstrated meaningful adaptive capacity as an expression of resilience. This study is intended to strengthen public awareness and encourage empathic, evidence-based interventions for children who are victims of domestic violence.